HYBRID LEARNING BASED TRAINING FOR ELEMENTARY SCHOOL TEACHERS IN IMPROVING PEDAGOGICAL COMPETENCE - Rudi Susilana; Nandang Rusmana; Gema Rullyana; Lutfi Nur; Ardiansah Ardiansah (PEDAGOGIA, 2022)
Competence possessed by teachers in carrying out educational activities is required to utilize ICT as a learning tool—education and training activities for teachers to improve competency. Educators can optimally utilize and use ICT as a learning aid, especially for educators in elementary schools. One of them is the use of ICT with the use of a learning management system (LMS). The study aimed to determine hybrid learning-based training for elementary school teachers in improving pedagogic competence. Implementing education and training activities for elementary school teachers was carried out at SD Negeri Sukasenang, Singaparna District, Tasikmalaya Regency. The target participants for this activity were elementary school teachers throughout Tasikmalaya Regency. Two hundred teachers from various sub-districts in Tasikmalaya Regency attended this training and education, divided into five classes. In this activity, there were 11 topics of training material, and each participant took part in 32 hours of lessons delivered using the hybrid learning method by utilizing a learning management system (LMS). The study results show that applying the LMS-based hybrid learning model of training and mentoring can be said to be effective. This is indicated by the level of attendance of participants in training and mentoring activities using LMS-based hybrid learning, the participants' understanding of the material provided, and the level of motivation of participants after participating in training and mentoring activities using LMS-based hybrid learning shows a good category.